2022
DOI: 10.3390/cimb44050147
|View full text |Cite
|
Sign up to set email alerts
|

3,3′,4,5′-Tetramethoxy-trans-stilbene Improves Insulin Resistance by Activating the IRS/PI3K/Akt Pathway and Inhibiting Oxidative Stress

Abstract: The potential anti-diabetic effect of resveratrol derivative, 3,3′,4,5′-tetramethoxy-trans-stilbene (3,3′,4,5′-TMS) and its underlying mechanism in high glucose (HG) and dexamethasone (DXMS)-stimulated insulin-resistant HepG2 cells (IR-HepG2) were investigated. 3,3′,4,5′-TMS did not reduce the cell viability of IR-HepG2 cells at the concentrations of 0.5–10 µM. 3,3′,4,5′-TMS increased the potential of glucose consumption and glycogen synthesis in a concentration-dependent manner in IR-HepG2 cells. 3,3′,4,5′-TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…AKT activation can further induce glycogen synthesis through increasing phosphorylation of GSK3β and inhibit gluconeogenesis through increasing phosphorylation of FoxO1 [ 47 ]. A certain degree of oxidative stress can reduce insulin sensitivity by suppressing the AKT signaling pathway leading to insulin resistance [ 45 , 48 ]. Once the phosphorylation of AKT is inhibited, the phosphorylation levels of GSK3β and FoxO1 also decrease, which causes decreased glycogen synthesis and increased gluconeogenesis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKT activation can further induce glycogen synthesis through increasing phosphorylation of GSK3β and inhibit gluconeogenesis through increasing phosphorylation of FoxO1 [ 47 ]. A certain degree of oxidative stress can reduce insulin sensitivity by suppressing the AKT signaling pathway leading to insulin resistance [ 45 , 48 ]. Once the phosphorylation of AKT is inhibited, the phosphorylation levels of GSK3β and FoxO1 also decrease, which causes decreased glycogen synthesis and increased gluconeogenesis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A certain degree of oxidative stress can reduce insulin sensitivity by suppressing the AKT signaling pathway leading to insulin resistance [ 45 , 48 ]. Once the phosphorylation of AKT is inhibited, the phosphorylation levels of GSK3β and FoxO1 also decrease, which causes decreased glycogen synthesis and increased gluconeogenesis [ 48 , 49 ]. Therefore, decreased insulin sensitivity in mice is often accompanied by reduced expression levels of phosphorylated AKT, FoxO1 and GSK3β (normalized to unphosphorylated AKT, FoxO1 and GSK3β, respectively) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…An insulin resistant cell model was triggered by a combination of DXMS and high glucose as previously reported. 32,33 DXMS exacerbates the onset of insulin resistance and oxidative stress in a hyperglycemic environment by interfering with insulin signaling and impairing mitochondrial function. 34 HepG2 cells were pretreated with DXMS (30 μM, dissolved in ethanol) and d -glucose (50 mM final concentration) for 48 h. Thereafter, the experimental groups were treated with different concentrations of 3,4′,5-TMS (0.5 and 1 μM) for 16 h. The group not treated with DXMS, d -glucose and 3,4′,5-TMS served as the control.…”
Section: Methodsmentioning
confidence: 99%
“…Javed et al (2022) depicted that resveratrol (30 mg/kg, intraperitoneal injection) could reduce IR and restore its normal histopathology in enteroendocrine L cells by facilitating the expression of glucagon‐like peptide‐1(GLP‐1). Also, Tan et al (2022) showed that resveratrol derivative (3,3′,4,5′‐tetramethoxy‐trans‐stilbene, 3,3′,4,5′‐TMS) (0.5–10 μM) could fight against IR in HepG2 cells of which the underlying mechanism was activating insulin receptor substrate‐1 (IRS)/PI3K/Akt signaling pathway and upregulating NF‐E2‐related factor (Nrf2). Second, glycometabolism disorder is the principal characteristic of DM, and it is of great significance for treating DM to correct the glycemetabolism disorder (Li et al, 2022).…”
Section: Beneficial Effects and Underlying Mechanisms Of Resveratrol ...mentioning
confidence: 99%